Initiatives, regulations and procedures to combat money laundering in the Bahamas. - Francis, Carlene Y. (1992)
Describes efforts by Bahamas to prevent abuse of the financial system, including the bank/trust licencing system, the adoption of a 'Code of Conduct' by the Association of International Banks and Trust Companies (AIBT) in 1985, and making money laundering a criminal offense.